1955
DOI: 10.1021/ja01626a037
|View full text |Cite
|
Sign up to set email alerts
|

Neighboring Carbon and Hydrogen. XIX. t-Butylcyclohexyl Derivatives. Quantitative Conformational Analysis

Abstract: The layers were separated, and the aqueous portion extracted several times with 5-ml. portions of methylene chloride. The combined methylene chloride extracts were washed with water, dried over magnesium sulfate and concentrated. The residual 2-chloro-2,3,3-trimethyIbutane was purified by sublimation under reduced pressure. The recovery was 0.60 g.The following procedures were used to convert the chloride samples to silver chloride for radioactive assay. A portion of the aqueous hydrochloric acid solution cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
235
0
4

Year Published

1975
1975
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 512 publications
(242 citation statements)
references
References 3 publications
(5 reference statements)
3
235
0
4
Order By: Relevance
“…6), because the steric hindrance of the tert-butyl group is so large that it is known to be fixed in the equatorial position. 8 ) When the commercially available mixture of cis-and trans-4-t-Bu-C 6 -OL (33 : 67) was subjected to microbial oxidation (300 mg/50 ml medium, 30°C, 5 days) by C. equi, the cis/trans ratio of recovered alcohol (total 72%) changed to 11 : 89. These results strongly suggested that trans-4-t-Bu-C 6 -OL was not or little, if any, affected by the bacterium.…”
Section: !-Bu~hmentioning
confidence: 99%
See 2 more Smart Citations
“…6), because the steric hindrance of the tert-butyl group is so large that it is known to be fixed in the equatorial position. 8 ) When the commercially available mixture of cis-and trans-4-t-Bu-C 6 -OL (33 : 67) was subjected to microbial oxidation (300 mg/50 ml medium, 30°C, 5 days) by C. equi, the cis/trans ratio of recovered alcohol (total 72%) changed to 11 : 89. These results strongly suggested that trans-4-t-Bu-C 6 -OL was not or little, if any, affected by the bacterium.…”
Section: !-Bu~hmentioning
confidence: 99%
“…Strikingly, the reactivity of cyclooctanol was very low. While both smaller and larger ring-sized alcohols such as cyclopentanol, cyclohexanol, were oxidized smoothly, medium ring-sized alcohols (n = 7,8) were…”
Section: !-Bu~hmentioning
confidence: 99%
See 1 more Smart Citation
“…A widely accepted method of locking the mobile cyclohexane system into one of two chair conformations has been the use of the t-butyl group (Winstein & Holness, 1955). Any comparison of data on cyclohexane systems locked into two different conformations relies on assumptions that the cyclohexane ring is unaltered by the different substitutions.…”
Section: Introductionmentioning
confidence: 99%
“…It was thought that the bulky tertiarybutyl group would cause a large puckering of the cyclopentane ring and the ring would be "locked" in an envelope or half-chair conformation, analogous to the ^-butylcyclohexyl compounds studied (92,93). A compar ison of this system with the unsubstituted cyclopentyl compounds and the previously studied phenyl-, methyl-and jL-propylcyclopentyl compounds should give a good indication of the steric requirements of a _t-butyl group and its effect on the conformation of the five-membered ring.…”
Section: Syntheticmentioning
confidence: 99%